Alleviating Work Exhaustion, Improving Professional Fulfillment, and Influencing Positivity Among Healthcare Professionals During COVID-19: A Study on Sudarshan Kriya Yoga - Kanchibhotla, Divya; Harsora, Prateek; Gupte, Poorva; Mehrotra, Saurabh; Sharma, Pooja; Trehan, Naresh (Frontiers in Psychology, 2022)
Demanding work-life and excessive workload, the conflict between professional and personal lives, problems with patients and those related to the occurrence of death and high risk for their own life are few factors causing burnout, disengagement, and dissatisfaction in professional life among Healthcare Professionals. The situation worsened during COVID-19 pandemic. It is of utmost importance to find effective solutions to mitigate the stress and anxiety adversely affecting the mental well-being and professional life for Healthcare professionals. This study was designed to examine the efficacy of Sudarshan Kriya Yoga (SKY) or alleviating work exhaustion, improving professional fulfillment, and influencing positivity among HCPs during COVID-19. A comparative observation before the intervention (Pre), after the intervention (Post), and 30 days after the intervention (Day 30) among experimental group (29 physicians) and control group (27 physicians), it was found that immediately after SKY HCPs experienced a significant improvement in professional fulfillment(p=0.009), work exhaustion (0.008), positive affect(p=0.02) and negative affect (p<0.001) compared to the control group. The effect of SKY continued on Day 30 for professional fulfillment and positive and negative effects. Findings suggest that SKY elevated professional fulfillment among the HCPs during the COVID-19 pandemic and reduced their work exhaustion and the negative impact on their mental health. Sudarshan Kriya Yoga can aid HCPs in maintaining their well-being during unprecedented challenges.